Complex biological patterns of hematology parameters in childhood necessitating age‐ and sex‐specific reference intervals for evidence‐based clinical interpretation. (12th August 2020) - Bohn, Mary Kathryn; Higgins, Victoria; Tahmasebi, Houman; Hall, Alexandra; Liu, En; Adeli, Khosrow; Abdelhaleem, Mohammed
Abstract: Introduction: Hematology laboratory parameters are among the most routinely ordered tests in support of adult and pediatric care. However, appropriate interpretation of test results has been a challenge in pediatrics since accurate and up‐to‐date reference intervals that reflect the dynamic physiological changes associated with growth and development have not been available. Critical gaps continue to exist in pediatric hematology reference intervals for modern laboratory platforms. To address this gap, this study establishes age‐ and sex‐specific reference intervals for 25 hematology parameters in the CALIPER cohort of healthy children and adolescents using a common platform, the Sysmex XN‐3000 analytical system. Methods: Fresh whole blood samples collected from a total of 641 healthy children and adolescents (birth to <21 years) with informed consent were analyzed for 25 hematological parameters on the Sysmex XN‐3000 Hematology Analyzer. Age‐ and sex‐specific reference standards were calculated based on Clinical and Laboratory Standards Institute guidelines. Results: Of the 25 analytes assessed, 19 required age‐partitioning and seven required sex‐partitioning (ie, red blood cell count, hemoglobin, hematocrit, mean corpuscular volume, red blood cell distribution width—SD, red blood cell distribution width—CV, and monocyte percentage). Age‐ and sex‐specific differences mostly coincided with the onset of puberty. Conclusion: This study establishes a comprehensive database of pediatric reference intervals for hematology parameters in the CALIPER cohort using the widely used Sysmex XN‐3000 analytical platform. These data highlight the dynamic hematological profile observed in healthy children and adolescents and the need for reference interval stratification by age and sex.